Investigação qualitativa: contributos para a sua melhor compreensão e condução - de Freitas, M. Cristina V. (2013)
This paper offers some reflections about the characteristics of qualitative research, outlined in its historical evolution, with particular focus to the last decades of the 20th century, relating them to issues of varying order. It also clarifies the profile and role of qualitative researchers, explaining some criteria used to evaluate these studies. To accomplish these goals, it is performed a selective literature review, by researching reference works, in recent periods, in order to capture its trends. There are several conclusions that emerge from this research. Qualitative studies are founded on approaches that are supported on a general paradigm, defined by ontological, epistemological, methodological, axiological and rhetorical aspects. Qualitative studies have four cardinal points: agreement between theories and methods; use of subjects’ perspectives; use of self-reflection; and use of various approaches and methods. They also have a flexible and emergent design, combining it with an inductive, holistic, humanistic, and naturalistic approach. The nature of the problems and the personal inclinations of the qualitative researchers have influences in its conduction. Qualitative researchers must control the subjectivity, and act with tolerance and faith. We evaluate the qualitative studies by its consistency, authenticity, transfer, variation, and fit. All these criteria have a proper paradigm of analysis, and we cannot fit them in another context.